Unraveling the Mechanism of Electrically Induced Adhesive Debonding: A Spectro‐Microscopic Study. Issue 1 (2nd December 2021) - Anduix‐Canto, Clara; Peral, Daniel; Pérez‐Padilla, Víctor; Diaz‐Rovira, Anna Maria; Belmez Lledó, Alejandro; Orme, Christine A.; Petrash, Stanislas; Engels, Thomas; Chou, Kang Wei
Abstract: The design of new electrically debondable adhesives has been an area of enormous interest for the recycling, repair, and reuse of electrical components for the last decade. However, the complexity of analyzing the debonding process under real conditions is a major obstacle for elucidating the mechanism. Here, a general mechanism for the electrical debonding of ionic acrylic adhesives based on imidazolium ionic liquids is reported. Using synchrotron‐based characterization techniques, in situ experiments mimicking real debonding conditions allowed for the first time the recording of ionic diffusion and chemical reactions during the debonding process. Diffusion of ionic species toward the electrodes triggers the debonding via electrochemical reactions at the adhesive–substrate interfaces. The selection of ionic adhesive chemistry and electrodelamination conditions will eventually determine the type of adhesive failure. A detailed understanding of the mechanism allows the development of new electrically debondable adhesives, which is crucial to promote circular economy and a more sustainable environment. Abstract : In situ synchrotron techniques are used to unravel the mechanism of electrically induced adhesive debonding. Acrylic adhesives containing imidazolium‐based ionic liquids present both anodic and cathodic delamination from aluminum substrates due to electrochemical reactions occurring at the interfaces. Understanding of the mechanism is essential for the design of new adhesives that allow reuse, repair, and recycling promoting a circular economy.